1997
DOI: 10.1159/000119332
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Acute-Phase Proteins during Lithium Potentiation of Antidepressants in Refractory Depression

Abstract: This study was performed on 32 patients with refractory depression in whom lithium was added to antidepressant treatment in order to potentiate the therapeutic effect, and in 20 healthy controls. Plasma concentration of three acute-phase proteins (APPs): C-reactive protein, alpha-1-acid glycoprotein (AGP) and alpha-1-antichymotrypsin (ACT) as well as microheterogeneity of AGP and ACT were measured, before and after 4 weeks of lithium addition to antidepressants. Before Li addition, all patients studied had ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 23 publications
3
85
0
3
Order By: Relevance
“…Effective lithium treatment diminished the plasma concentration of acute phase proteins, a marker for the activation of the inflammatory response system. 31,57 Lithium also reduced the soluble IL-6 receptors and the soluble IL-2 receptors to a normal level in symptomatic rapid cycling bipolar patients with a mild inflammatory response system. 29 Recently, it was found that lithium caused an increase in IL-4 and IL-10, classified as Th-2 cytokines, and a decrease in IL-2 and IFN-␥, classified as Th1 cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…Effective lithium treatment diminished the plasma concentration of acute phase proteins, a marker for the activation of the inflammatory response system. 31,57 Lithium also reduced the soluble IL-6 receptors and the soluble IL-2 receptors to a normal level in symptomatic rapid cycling bipolar patients with a mild inflammatory response system. 29 Recently, it was found that lithium caused an increase in IL-4 and IL-10, classified as Th-2 cytokines, and a decrease in IL-2 and IFN-␥, classified as Th1 cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…The impact of epigenetic changes in FKBP5 are in part related to the induction of glucocorticoid resistance and reduced hormonal (glucocorticoid) control of inflammatory responses as reflected by decreased sensitivity to the synthetic glucocorticoid dexamethasone in vitro following LPS stimulation (Klengel et al, 2013). Relative to treatment response, it should also be noted that increased inflammatory markers have been associated with treatment nonresponse, such that patients with evidence of increased inflammation before antidepressant treatment exhibit reduced treatment responsiveness, and patients who are defined as treatment resistant exhibit increased inflammatory markers (Sluzewska et al, 1997;Lanquillon et al, 2000;Raison et al, 2013a, b;Strawbridge et al, 2015).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
“…Depressive patients who do not respond to antidepressant therapy have been shown to have higher levels of inflammatory cytokines and CRH in the circulation, compared with patients who are not resistant to this therapeutic procedure [119] (Figure 1).…”
Section: Corticotrophin-releasing Hormone (Crh)mentioning
confidence: 99%